Saturday

July 26, 2014

July 26, 2014

Total # Posts: 1,681

**Trigonometry**

Reiny, Are you sure that the height of the Washington Monument is 171.7 FEET?

**Trigonometry**

Remark: ctg is cotangent ( cot )

**Trigonometry**

Angle in point A = 32 ° tan 32 ° = H / L L = H / tan 32 ° = H * ctg 32 ° Angle in point B = 38 ° tan 38 ° = H / ( L - 55 ) L - 55 = H / tan 38 ° = H * ctg 38 ° L - 55 = H * ctg 38 ° Add 55 to both sides L - 55 + 55 = H * ctg 38 + 55 L = H * ...

**math**

4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 = 8 * 4 ^ 8 = 2 * 4 * 4 ^ 8 = 2 * 4 ^ 9 = 2 * 262144 = 524288

**Algebra**

x = a number L = x - 2 W = L + 4 = x - 2 + 4 = x + 2 A = L * W = ( x - 2 ) * ( x + 2 ) = x ^ 2 - 2 ^ 2 = x ^ 2 - 4 Answer C _____________________________________ Remark: ( a - b ) ( a + b ) = a ^ 2 - b ^ 2 _____________________________________

**math**

a = first leg b = a + 1 = second leg c = b + 1 = a + 1 + 1 = a + 2 = hypotenuse c ^ 2 = a ^ 2 + b ^ 2 ( a + 2 ) ^ 2 = a ^ 2 + ( a + 1 ) ^ 2 __________________________________ Remark: ( a + b ) ^ 2 = a ^ 2 + 2 * a * b + b ^ 2 __________________________________ a ^ 2 + 2 * a * 2...

**math**

I will not answer all the questions in your homework.

**math**

( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2 (4 x - 3 y ) ^ 2 = (4 x ) ^ 2 - 2 * 4 x * 3 y + ( 3 y ) ^ 2 = 16 x ^ 2 - 24 x y + 9 y ^ 2

**math**

1 yd = 3 * 12 = 36 ft 36 * 2.54 = 91.44 1 yd = 91.44 cm

**math**

n = numbers of persons 100 + 20 * n = 25 + 25 * n 100 + 20 n = 25 + 25 n Subtract 25 to both sides 100 + 20 n - 25 = 25 + 25 n - 25 75 + 20 n = 25 n Subtract 20 n to both sides 75 + 20 n - 20 n = 25 n - 20 n 75 = 5 n Divide both sides by 5 75 / 5 = 5 n / 5 15 = n n = 15 Proof:...

**math**

C ° = ( 5 / 9 ) * ( F ° - 32 ) ( 5 / 9 ) * ( 95 - 32 ) = ( 5 / 9 ) * 63 = 315 / 9 = 35 ° C

**math**

P = 2 * ( W + L ) P = 24 W = 4 24 = 2 * ( 4 + L ) 24 = 2 * 4 + 2 * L 24 = 8 + 2 L Subtract 8 to both sides 24 - 8 = 8 + 2 L - 8 16 = 2 L Diwide both sides by 2 16 / 2 = 2 L / 2 8 = L L = 8

**math**

5 / 8 = 5 * 3 / ( 8 * 3 ) = 15 / 24 1 / 3 = 8 * 1 / ( 8 * 3 ) = 8 / 24 2 5 / 8 + 1 / 3 = 2 + 5 / 8 + 1 / 3 = 2 + 15 / 24 + 8 / 24 = 2 + 23 / 24 = 2 * 24 / 24 + 23 / 24 = 48 / 24 + 23 / 24 = 71 / 24

**Math**

| x + 4 | = | 3 x + 10 | x + 4 = 3 x + 10 OR x + 4 = - ( 3 x + 10 ) 1 ) x + 4 = 3 x + 10 Subtract x to both sides x + 4 - x = 3 x + 10 - x 4 = 2 x + 10 Subtact 4 to both sides 4 - 4 = 2 x + 10 - 4 0 = 2 x + 6 Subtract 2 x to both sides 0 - 2 x = 2 x + 6 - 2 x - 2 x = 6 Divide ...

**RE: ALGEBRA**

Obviously x = 0 25 x ^ 2 - 10 x = 0 25 * 0 ^ 2 - 10 * 0 = 0 25 * 0 - 10 * 0 = 0 0 - 0 = 0 0 = 0 and 25 x ^ 2 - 10 x = 0 Divide both sides by 5 x 25 x ^ 2 / 5 x - 10 x / 5 x = 0 / 5 x 5 * 5 * x * x / 5 x - 2 * 5 x / 5 x = 0 5 x - 2 = 0 Add 2 to both sides 5 x - 2 + 2 = 0 + 2 5 ...

**Inequalities & Absolute value**

For x = - 2 | 2 x + 4 | < 5 | 2 * ( - 2 ) + 4 | < 5 | - 4 + 4 | < 5 | 0 | < 5 0 < 5 Correct | 5 - 3 x | < 9 | 5 - 3 * ( - 2 ) | < 9 | 5 + 6 | < 9 | 11 | < 9 11 < 9 Not correct 1 correct solution For x = - 1 | 2 x + 4 | < 5 | 2 * ( - 1 ) + 4 | &...

**Math**

When multiplying any number by 0, you get 0. ( 4 / 3 ) * 0 = 0 0 * ( 1 / 2 ) = 0 4/3 multiply by 0 multiply by 1/2 = 0

**math**

xm = 6 ym = 2 x1 = 3 y1 = 5 xm = ( x1 + x2 ) / 2 6 = ( 3 + x2 ) / 2 Multiply both sides by 2 6 * 2 = 2 * ( 3 + x2 ) / 2 12 = 3 + x2 Subtract 3 to both sides 12 - 3 = 3 + x2 - 3 9 = x2 x2 = 9 ym = ( y1 + y2 ) / 2 2 = ( 5 + y2 ) / 2 Multiply both sides by 2 2 * 2 = 2 * ( 5 + y2 ...

**Math**

9,999 & 10,000 9 + 9 + 9 + 9 = 36 1 + 0 + 0 + 0 + 0 = 1

**Math**

Probably a rectangle . The sides of a rectangle are in the ratio 2 : 1

**maths**

a n = 60 / n a1 = 60 / 1 = 60 a2 = 60 / 2 = 30 a3 = 60 / 3 = 20 a4 = 60 / 4 = 15 a5 = 60 / 5 = 12 a6 = 60 / 6 = 10 12 and 10

**algebra**

9 x + y = 2 Subtract 9 x to both sides 9 x + y - 9 x = 2 - 9 x y = 2 - 9 x –4 x – y = – 17 –4 x – ( 2 - 9 x ) = – 17 - 4 x - 2 - ( - 9 x ) = - 17 - 4 x - 2 + 9 x = - 17 - 4 x + 9 x - 2 = - 17 5 x - 2 = - 17 Add 2 to both sides 5 x - 2 + 2 = - 17 +...

**Geometry**

The altitude to the base of an isosceles triangle bisects the vertex angle. The altitude to the base of an isosceles triangle bisects the base. L - is the length of a leg B - is the base A - is the altitude A = square root [ L ^ 2 - ( B / 2 ) ^ 2 ]

**Algebra, can some show me how to set this up**

In equation : f(x) = x − 7 replace x with given numbers. f ( 13 ) = 13 - 7 = 6 f ( - 6 ) = - 6 - 7 = - 13 f ( p ) = p - 7

**Math**

30.2 t + 587 = 1432.6 Subtract 587 to both sides 30.2 t + 587 - 587 = 1432.6 - 587 30.2 t = 845.6 Divide both sides by 30.2 t = 845.6 / 30.2 t = 28 1990 + 28 = 2018

**Maths**

Total expenses : 1 / 2 + 1 / 4 + 1 / 5 = 10 / 20 + 5 / 20 + 4 / 20 = 19 / 20 1 - 19 / 20 = 20 / 20 - 19 / 20 = 1 / 20 A person save 1 / 20 part of salary. S / 20 = 50 M ultiply both sides by 20 S = 20 * 50 = 1000

**Math (check answer plz)**

The probability of guessing the correct answer for one question = 1 / 2 ( 1 / 2 ) ^ 12 = 1 / 2 ^ 12 = 1 / 4096 Answer A

**Maths!**

100 , 105, 110, ... 290 , 295 ,300 That is arithmetic progression. The initial term of this arithmetic progression is a1 = 100 The common difference of successive members is d = 5 The n-th term this arithmetic progression an = 300 Use formula for n-th term of the sequence : an...

**algebra**

y = 5 x Divide both sides by 5 y / 5 = x x = y / 5 d = 55 t Divide both sides by 55 d / 55 = t t = d / 55

**Math**

A = h ^ 2 / sqrt ( 3 ) A = 9 ^ 2 / sqrt ( 3 ) A = 81 / sqrt ( 3 ) A = 27 * 3 / sqrt ( 3 ) A = 27 * sqrt ( 3 ) * sqrt ( 3 ) / sqrt ( 3 ) A = 27 * sqrt ( 3 ) Answer J

**pre calculus**

x1 = - 2 x2 = 5 x3 = - 6 y = ( x - x1 ) ( x - x2 ) (x - x3 ) y = [ x - ( - 2 ) ] ( x - 5 ) [ x - ( - 6 ) ] y = ( x + 2 ) ( x - 5 ) ( x + 6 ) y = x ^ 3 + 3 x ^ 2 - 28 x - 60

**algebra**

and x4 - x3 = 7 - 5 = 2

**algebra**

Reiny c) isn't correct answer In w o l f r a m a l p h a . c o m type: interpolate (1,-3),(3,5),(5,11),(7,18) That is a cubic polynomial.

**algebra**

Answer a) x1 = 1 , y1= - 2 x2 = 3 , y2 = 1 x3 = 5 , y3= 4 x4 = 7 , y4 = 7 x2 - x1 = 3 - 1 = 2 x3 - x2 = 5 - 3 = 2 x4 - x3 = 7 - 3 = 2 y2 - y1 = 1 - ( - 2 ) = 1 + 2 = 3 y3 - y2 = 4 - 1 = 3 y4 - y3 = 7 - 4 = 3 Numerically, y increases by 3 units for every 2 unit increase of x.

**math**

x = first number y = second number x + y = 45 Subtract x to both sides x + y - x = 45 - x y = 45 - x square root ( x * y ) = 18 Take square of both sides x * y = 18 ^ 2 x * y = 324 x * ( 45 - x ) = 324 x * 45 - x * x = 324 45 x - x ^ 2 = 324 Subtract 324 to both sides 45 x - x...

**Intermediate algebra**

2 x ^ 2 + 3 = 0 Subtract 3 to both sides 2 x ^ 2 + 3 - 3 = 0 - 3 2 x ^ 2 = - 3 Divide both sides by 2 x ^ 2 = - 3 / 2 Take square root of both sides x = + OR - square root ( - 3 / 2 ) x = + OR - i * square root ( - 3 / 2 )

**Algebra 1--Please, check my answer!**

Correct

**Maths**

A x = b - c x Add c x to both sides A x + c x = b - c x + c x A x + c x = b x ( A + c ) = b Divide both sides by ( A + c ) x = b / ( A + c )

**Algebra 1--Please, check my answer!**

2 t / 4 t ^ 2 + 2 / t = 2 t / ( 2 * 2 * t * t ) + 2 / t = 1 / 2 t + 2 / t = 1 / 2 t + 2 * 2 / 2 t = 1 / 2 t + 4 / 2 t = ( 1 + 4 ) / 2 t = 5 / 2 t Correct Answer

**Algebra can someone guide me**

a ) f ( 13 ) = 13 - 7 = 6 a ) f ( - 6 ) = - 6 - 7 = - 13 c ) f ( p ) = p - 7

**Algebra can someone guide me**

Correction: f ( - 6 ) = - 6 - 7 = - 13

**Algebra can someone guide me**

f ( x) = x − 7 Just replace x with the given values. f ( 13 ) = 13 - 7 = 6 f ( 6 ) = 6 - 7 = 1 f ( p ) = 9 - 7

**Geometry**

V1 = Volume of one sphere: V1 = ( 1 / 6 ) * pi * d ^ 3 V = 30 * V1 V = 30 * ( 1 / 6 ) * pi * d ^ 3 V = ( 30 / 6 ) * pi * d ^ 3 V = 5 * pi * d ^ 3 3,392.92 = 5 * pi * d ^ 3 3,392.92 = 5 * 3.1416 * d ^ 3 3,392.92 = 15.708 * d ^ 3 Divide both sides by 15.708 3,392.92 / 15.708 = 1...

**maths**

Remark: Length and width have path 2 meter wide for both sides. That's why we need to reduce their sizes by 2 m * 2 m Area of rectangle : A = a * b where a = L - 2 * 2 = 40 - 2 * 2 = 40 - 4 = 36 m b = W - 2 * 2 = 25 - 2 * 2 = 25 -4 = 21 m So : A = a * b = 36 * 21 = 756 m ^ 2

**maths**

A = ( 40 - 2 * 2 ) * ( 25 - 2 * 2 ) = ( ( 40 - 4 ) * ( 25 - 4 ) = 36 * 21 = 756 m ^ 2

**math**

The graph of a quadratic function is a parabola. If you want to see graph In google type: functions graphs online When you see list of results click on: rechneronline.de/function-graphs When page be open in blue recatacangle type: x ^ 2 + 1 Then click option Draw

**math**

For rule you must give more numbers in Input and Output Table

**maths**

( a + b ) ( a - b ) = a ^ 2 - b ^ 2 ( square root 7 + square root 5 ) ( square root 7 - square root 5 ) = ( square root 7 ) ^ 2 - ( square root 5 ) ^ 2 = 7 - 5 = 2

**maths**

520 - 5 t ^ 2 = 0 520 = 5 t ^ 2 Divide both sides by 5 104 = t ^ 2 t = sqrt ( 104 ) = 10. 198 sec

**math**

[ ( 2600 - 2000 ) / 2000 ] * 100 % = ( 600 / 2000 ) * 100 % = 0.3 * 100 % = 30 %

**Math**

0.8 / 1.6 = 0.5 0.4 / 0.8 = 0.5 0.2 / 0.4 = 0.5 Geometric progression with common ratio q =0 .5

**Math**

360 ° = 2 pi rad 360 ° / 23 = 2 pi / 23 rad

**I need to know how to work this Maths Problem**

PsyDAG Can you explain how 38 - 2 square root ( 62 ) IS NOT EQUAL 2 * ( 19 - square root ( 62 ) )

**I need to know how to work this Maths Problem**

What is your question? - 2 square root ( 62 )+ 38 = 38 - 2 square root ( 62 )= 2 * ( 19 - square root ( 62 ) ) So what?

**math**

x * y = x - y + 25 Add y to both sides x * y + y = x - y + 25 + y x * y + y = x + 25 y ( x + 1 ) = x + 25 Divide both sides by x + 1 y = ( x + 25 ) / ( x + 1 ) Long Division of Polynomials y = 1 + 24 / ( x + 1 ) You have infinite numbers of solutions, so you must give one more...

**math Question**

a 5 = 160 a 6 = a 5 * q = 160 * q a 7 = a 6 * q = a 5 * q * q = 160 * q ^ 2 = 40 160 q ^ 2 = 40 Divide both sides by 40 4 q ^ 2 = 1 Divide both sides by 4 q ^ 2 = 1 / 4 Take square root of both sides q = + OR - 1 / 2 All number in progression is positive so q = 1 / 2 a 6 = a 5...

**Algebra 2**

315 ° = 360 ° - 45 ° cos ( 360 ° - theta ) = cos ( theta ) cos ( 360 ° - 45 °) = cos ( 45 ° ) = square root ( 2 ) / 2

**math**

For x = - 3 y = ( 1 / 3 ) | - 3 | - 2 = ( 1 / 3 ) * 3 - 2 = 1 - 2 = - 1 for x = - 2 y = ( 1 / 3 ) | - 2 | - 2 = ( 1 / 3 ) * 2 - 2 = 2 / 3 - 2 = 2 / 3 - 6 / 3 = - 4 / 3 for x = - 1 y = ( 1 / 3 ) | - 1 | - 2 = ( 1 / 3 ) * 1 - 2 = 1 / 3 - 2 = 1 / 3 - 6 / 3 = - 5 / 3 for x = 0 y =...

**math**

For x = - 3 y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 3 ) ^ 2 + 3 = - 2 * 9 + 3 = - 18 + 3 = - 15 for x = - 2 y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 2 ) ^ 2 + 3 = - 2 * 4 + 3 = - 8 + 3 = - 5 for x = - 1 y = - 2 ( x ) ^ 2 + 3 = - 2 * ( - 1 ) ^ 2 + 3 = - 2 * 1 + 3 = - 2 + 3 = - 1 for x = 0 y...

**algebra**

7 - | m - 1 | = 3 Subtract 3 to both sides 7 - | m - 1 | - 3 = 3 - 3 4 - | m - 1 | = 0 Add | m - 1 | to both sides 4 - | m - 1 | + | m - 1 | = 0 + | m - 1 | 4 = | m - 1 | | m - 1 | = 4 + OR - ( m - 1 ) = 4 1 solution : m - 1 = 4 Add 1 to both s ides m = - 1 + 1 = 4 + 1 m = 5 2...

**Math**

That is calculus question. a = length b = width P = Perimeter A = Area P = 2 a + 2 b = 2 ( a + b ) 24 = 2 ( a + b ) Divide both sides by 2 12 = a + b a + b = 12 Subtract a to both sides a + b - a = 12 - a b = 12 - a A = a * b = a * ( 12 - a ) A = 12 a - a ^ 2 The function has ...

**Math 2**

1 quart = 0.946353 liters The closest amount of milk = 1 liter. By the way in google type : units conversion. You will find many links.

**Algebra 1**

In google type : quadratic equation online When you see list of results click on : Free Online Quadratic Equation Solver: Solve by Quadratic... When page be open click option : Solve by Completing the Square Then in rectangle type : - x ^ 2 - 5 x = - 5 and click option : solve...

**algebra**

You're welcome.

**algebra**

log ( a ^ n ) = n * log ( a ) log ( 1 / a ) = - log ( a ) log ( a * b ) = log ( a ) + log ( b ) 64 = 8 * 8 log ( 64 ) = log ( 8 ) + log ( 8 ) log ( 64 ) = 2 * log ( 8 ) 8 ^ x = 1 / 64 x * log ( 8 ) = log ( 1 / 64 ) x * log ( 8 ) = - log ( 8 * 8 ) x * log ( 8 ) = - [ log ( 8 ) ...

**algebra**

2 x + y = 5 Subtract 2 x to both sides 2 x + y - 2 x = 5 - 2 x y = 5 - 2 x y = - 2 x + 5 y ^ 2 - 2 y = - 2 x + 5 ( - 2 x + 5 ) ^ 2 - 2 * ( - 2 x + 5 ) = - 3 x + 5 _______________________________________ Remark : ( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2 _______________________...

**mat117**

In google type : quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver: Solve by Quadratic... When page be open in rectanlgle type: -5 x ^ 2 + 8x + 9 = 0 and click option : solve it! You will see solution step - by - tep

**math**

M * P = 300 J Divide both sides by 300 M * P / 300 = 300 J / 300 M * P / 300 = J J = M P / 300 = P M / 300 Answer D

**math**

M = 300 J / P Multiply both sides by P M * P = 300 J * P / P M * P = 300 J Divide both sides by J M * P / 300 = 300 J / 300 M * P / 300 = J J = M P / 300 = P M / 300 Answer D

**Math7**

For x = - 9 y = 4 x - 9 = 4 * ( - 9 ) - 9 = - 36 - 9 = - 45 For x = 3 y = 4 x - 9 = 4 * 3 - 9 = 12 - 9 = 3 For x = - 6 y = 4 x - 9 = 4 * ( - 6 ) - 9 = - 24 - 9 = - 33 For x = 5 y = 4 x - 9 = 4 * 5 - 9 = 20 - 9 = 11 If youe expression mean : y = - 4 x -9 then ( 5 , - 28 ) is no...

**Algebra 1 (Reiny)**

In google type : quadratic equation online When you see list of results click on : Free Online Quadratic Equation Solver: Solve by Quadratic.. When page be open in rectangle type x ^ 2 + 2 = 0 and click option : solve it! You will see solution step by step Repeat that for equa...

**Algebra**

If (10 / 3x) + (4/3) = (7 + x) / (2x) mean 10 / ( 3 x ) + 4 / 3 = ( 7 + x ) / ( 2 x ) then Multiply both sides by x 10 * x / ( 3 x ) + 4 * x / 3 = x * ( 7 + x ) / ( 2 x ) 10 / 3 + 4 x / 3 = ( 7 + x ) / 2 Multiply both sides by 6 10 * 6 / 3 + 6 * 4 x / 3 = 6 *( 7 + x ) / 2 10 *...

**Math**

3 L / 2 = 18 Multiply both sides BY 2 3 L = 36 Divide both sides by 3 L = 12 ft

**Math**

P = 2 W + 2 L = 2 ( W + L ) = 40 2 ( W + L ) = 40 Divide both sides by 2 W + L = 20 W = 2 + L / 2 W + L = 20 2 + L / 2 + L = 20 2 + L / 2 + 2 L / 2 = 20 2 + 3 L / 2 = 20 Subtract 2 to both sides 2 + 3 L / 2 - 2 = 20 - 2 3 L / 2 = 18 Multiply both sides by 3 3 L = 36 Divide bot...

**algebra**

a ^ 2 - b ^ 2 = ( a + b ) ( a - b ) x ^ 2 + [ sqrt ( 15 ) ] ^ 2 = [ x + sqrt ( 15 ) ] * [ x - sqrt ( 15 ) ] sqrt mean "square root"

**Math**

x ^ a * x ^ b = x ^ ( a + b ) 2 ^ 2 * 2 ^ 8 = 2 ^ ( 2 + 8 ) = 2 ^ 10 ( 2.5 * 10 ^ 4 )( 4 * 10 ^ 3 ) = 2.5 * 4 * 10 ^ ( 4 + 3 ) = 10 * 10 ^ 7 = 10 ^ 1 * 10 ^ 7 = 10 ^ ( 1 + 7 ) = 10 ^ 8

**Algebra**

You must solve equation : 2 x ^ 2 + 6 x – 20 = 0 The solutions are : x = - 5 and 2 x-intercepts ( - 5 , 0 ) and ( 2 , 0 )

**Algebra**

3 x + 1 = 0 Subtract 1 from both sides 3 x + 1 - 1 = 0 - 1 3 x = - 1 Divide both sides by 3 3 x / 3 = - 1 / 3 x = - 1 / 3 x – 5 = 0 Add 5 from both sides x - 5 + 5 = 0 + 5 x = 5 The solutions are : - 1 / 3 and 5

**Algebra**

( x + 9 ) ^ 2 = 169 Take the square root of both sides x + 9 = 13 Subtract 9 from both sides x + 9 - 9 = 13 - 9 x = 4 The length of the original garden = 4 m

**algebra**

( 15 x ^ 2 + 10 x - 5 ) / 5 x = 5 ( 3 x ^ 2 + 2 x - 1 ) / 5 x = ( 3 x ^ 2 + 2 x - 1 ) / x = 3 x + 2 - 1 / x

**math**

h ( t ) = a t ^ 2 + b t + c h ( t ) = – 16 t ^ 2 + 20 t + 2 a = - 16 b = 20 c = 2 t - coordinate of minimum point t = - b / 2 a t = - 20 / [ 2 * - 16 ) ] t = - 20 / - 32 = 20 / 32 = 4 * 5 / ( 4 * 8 ) = 5 / 8 = 0.625 h - coordinate of minimum point h = - ( b ^ 2 - 4 a c ) ...

**Algebra**

You're welcome.

**Algebra**

If you think about Prentice Hall Algebra 1 9 - 6 then : The area of the photo will be half the area of the entire ad. Area of the photo = 7 * 5 = 35 in ^ 2 that is one half the area of the paper. So area of the paper = 70 in ^ 2 Now you must solve equation : ( 7 + x ) ( 5 + x ...

**math**

sqrt ( 3 x * y ^ 3 )* sqrt ( 2 x ^ 2 * y ) / sqrt ( 6 x ^ 3 * y ^ 4 ) = sqrt ( 3 x * y ^ 3 * 2 x ^ 2 * y ) / sqrt ( 6 x ^ 3 * y ^ 4 ) = sqrt ( 6 x ^ 3 y ^ 4 ) / sqrt ( 6 x ^ 3 y ^ 4 ) = 1

**MATH**

In google type : quadratic equation online When you see list of results click on : Free Online Quadratic Equation Solver: Solve by Quadratic When page be open in rectangle type : 3x^2+9x+3=0 and click option : solve it You will see solution step by step

**math (cant figure it out)**

Explanation r = d / 2 d = 2 r For that reason A = d * pi * ( d / 2 + h ) = 2 * r * pi * ( r + h )

**Algebra**

x = the cost of hot dog y = the cost of hamburger 3 x + 4 y = 13.5 4 x + 3 y = 12.75 3 x + 4 y = 13.5 - 4 x + 3 y = 12.75 ______________________ - x + y = 0.75 Add x to both sides - x + y + x = 0.75 + x y = 0.75 + x 4 x + 3 y = 12.75 4 x + 3 * ( 0.75 + x ) = 12.75 4 x + 2.25 +...

**MATH**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open click option Solve by Factoring (includes Factoring by Grouping) then in rectangle type 2x^2+5x+3=0 and click opt...

**MATH**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open in rectangle type 2x^2+5x+3=0 and click option: solve it!

**math**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open click option Solve by Factoring (includes Factoring by Grouping) then in rectangle type 2x^2 + 13x + 20=0 and cli...

**Math**

4 < = 2 c + 7 < = 21 Subbtract 7 4 - 7 < = 2 c + 7 - 7 < = 21 - 7 - 3 < = 2 c < = 14 Divide by 2 - 3 / 2 < = 2 c / 2 < = 14 / 2 - 3 / 2 < = c < = 7

**Math**

4 < = 2 c + 7 < = 21 Subbtract 7 4 - 7 < = 2 c + 7 - 7 < = 21 - 7 - 3 < = 2 c < = 14 Divide by 2 - 3 / 2 < = 2 c / 2 < = 14 / 2 - 3 / 2 < = c < = 7

**Math**

¡Ü

**math**

If f(x) -5x^2+7x+3 mean: f ( x ) = - 5 x ^ 2 + 7 x + 3 Then : f ( x ) = a x ^ 2 + b x + c f ( x ) = - 5 x ^ 2 + 7 x + 3 a = - 5 , b = 7 , c = 3 The x coordinate of the vertex ; x = - b / 2 a x = - 7 / ( 2 * ( - 5 ) ) x = - 7 / - 10 = 7 / 10

**Math**

Difference between second numbers is 11. 24 - 13 = 11 and 57 - 46 = 11 So: 111 ¨ 13 , 112 ¨ 24 , 113 ¨ 35 , 114 ¨ 46 , 115 ¨ 57 , 116 ¨ 68 , 117 ¨ 79

**algebra**

h = -1 6 t ^ 2 + vt v = 120 h = - 16 t ^ 2 + 120 t h = - 4 * 4 t ^ 2 + 4 * 30 t h = 4 t ( - 4 t + 30 ) 0 = 4 t ( - 4 t + 30 ) obviously solution : t = 0 ( initial point ) and - 4 t + 30 = 0 - 4 t = - 30 - 4 t / 4 = - 30 / - 4 t = 30 / 4 = 2 * 15 / ( 2 * 2 ) = 15 / 2 = 7.5 s

**Intermediate Algebra**

Correct The other sides : x and x + 1 where x + 1 is the hypotenuse So Pythagorean theorem: ( x + 1 ) ^ 2 = x ^ 2 + 5 ^ 2 x ^ 2 + 2 x + 1 = x ^ 2 + 25 Both x ^ 2 get cancelled 2 x + 1 = 25 2 x = 25 - 1 = 25 - 1 = 24 x = 24 / 2 = 12 m hypotenuse x + 1 = 12 + 1 = 13 m

**math**

1 lb = 0.45359237 kg 20 lb = 20 * 0.45359237 = 9.0718474 kg 20 lb = 9.1 kg rounded to the nearest tenth Remak : lb = pound

**Math! HELP!**

[ ( 3 / 2 ) b ^ 4 ] ^ 3 = [ ( 3 ^ 3 ) / ( 2 ^ 3 ) ] * ( b ^ 4 ) ^ 3 = ( 27 / 8 ) * b ^ ( 4 * 3 ) = ( 27 / 8 ) * b ^ 12 = 27 b ^ 12 / 8 ( 3 / 5 y ^ 4 )^ ( - 2 ) = [ ( 3 ^ ( - 2 ) ] / [ ( 5 ^ ( - 2 ) ] * [ y ^ 4 ^ ( - 2 ) ] = ( 1 / 3 ^ 2 ) / ( 1 / 5 ^ 2 ) * y ^ [ 4 * ( - 2 ) ] =...

**Algebra 1**

You're boring with your questions.

Pages: **1** | 2 | 3 | 4 | 5 | 6 | 7 | 8 | 9 | 10 | 11 | 12 | 13 | 14 | 15 | Next>>